Barbados : Staff Report for the 2004 Article IV Consultation. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2004)
This 2004 Article IV Consultation highlights that Barbados's economy has recovered partially from the 2001-02 recession, as real GDP grew by an estimated 2 percent in 2003, led by a recovery in the tourism sector. Inflation remained low at 1.5 percent, reflecting the currency peg. The external current account deficit widened in 2003, as merchandise exports declined and imports recovered from their low recession levels. Broad money growth decelerated in 2003, although it was still faster than GDP growth, and banks became increasingly liquid.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet